Greenwash vs. Brownwash: Exaggeration and Undue Modesty in Corporate Sustainability Disclosure - Kim, Eun-Hee; Lyon, Thomas P. (Organization Science, 2015)
Corporate greenwashing has accelerated in recent years, bringing in its wake growing skepticism about corporate green claims. Although a theory of the drivers and deterrents of greenwashing has begun to emerge, it is static in nature and does not incorporate the full range of ways in which firms can misrepresent their environmental performance. Our contribution is threefold. First, we extend the theory of organizational information disclosure to incorporate the possibility of undue modesty about a firm’s environmental, social, and governance practices. Second, we hypothesize about the drivers of exaggeration and undue modesty based on which of a firm’s stakeholders are salient at a given point in time; to do so, we place the firm within a dynamic context that has largely been missing in the prior literature. Third, we test our hypotheses using a data set that allows us to directly compare corporate green claims against actual performance. Results reveal that corporate output growth, deregulation, and low profits under deregulation significantly affect the choice between greenwashing and brownwashing. The effects of growth and profits are mitigated by external scrutiny.